A 3D printed microfluidic device for production of functionalized hydrogel microcapsules for culture and differentiation of human Neuronal Stem Cells (hNSC) - Alessandri, Kevin; Feyeux, Maxime; Gurchenkov, Basile; Delgado, Christophe; Trushko, Anastasiya; Krause, Karl-Heinz; Vignjević, Daniela; Nassoy, Pierre; Roux, Aurélien (Lab on a chip, 2016)
We present here a microfluidic device that generates sub-millimetric hollow hydrogel spheres, encapsulating cells and coated internally with a layer of reconstituted extracellular matrix (ECM) of a few microns thick. The spherical capsules, composed of alginate hydrogel, originate from the spontaneous instability of a multi-layered jet formed by co-extrusion using a coaxial flow device. We provide a simple design to manufacture this device using a DLP (digital light processing) 3D printer. Then, we demonstrate how the inner wall of the capsules can be decorated with a continuous ECM layer that is anchored to the alginate gel and mimics the basal membrane of a cellular niche. Finally, we used this approach to encapsulate human Neural Stem Cells (hNSC) derived from human Induced Pluripotent Stem Cells (hIPSC), which were further differentiated into neurons within the capsules with negligible loss of viability. Altogether, we show that these capsules may serve as cell micro-containers compatible with complex cell culture conditions and applications. These developments widen the field of research and biomedical applications of the cell encapsulation technology.